Examining the Relationship between Cooperative and Skilled Learning for Satisfaction of Students Studying Foreign Languages (Russian, English, and Arabic) - Sadeghi, Abbas; Davoudy, Seyyedeh Masoumeh (An Overview of Literature, Language and Education Research Vol. 5, 2024)
This study was performed to examine the relationship between cooperative learning and skilled learning with the satisfaction of students studying Russian, English, and Arabic languages. The students’ involvement and cooperation in the learning process are so important that some education professionals have proposed the participation rate of students in learning activities as a criterion for teachers’ evaluation. New and advanced theories on collaborative (cooperative) research in group learning suggest that learning is effective when the learner plays the central role. The research method was a correlational one. The study's statistical population included the students of fields Russian, English and Arabic languages at the University of Guilan in 2016 who were selected by the cluster sampling method accounting for 120 subjects. A researcher-made questionnaire was used to collect data. The data were analyzed using SPSS-18 software, the Pearson Correlation test, and the Linear Regression. According to the results, the variable of educational satisfaction was positively correlated with cooperative learning (r = 0.338) and skilled learning (r = 0.449). The skilled learning variable and then, the cooperative learning together explain 0.22 of the satisfaction variance. Also, the results revealed that cooperative learning and skilled learning have a significant effect on students’ satisfaction. Long-term changes in teaching practices depend on teachers understanding conceptually what cooperation is as well as being able to conduct cooperative learning lessons. In the school, staff members work in collegial support groups specially to increase teacher’s instructional expertise and success, task forces to plan and implement solutions to school-wide problems, and ad hoc decision-making groups to involve all staff members in important school decisions. Given the importance of this issue, we can say strengthening teaching skills can help increase the student’s satisfaction rate and quality of higher education. In practice, it is also suggested that cooperative and skilled learning approaches will be taught to teachers and included in the in-service training courses.